A plasmonic modulator based on metal-insulator-metal waveguide with barium titanate core - Babicheva, Viktoriia E.; Lavrinenko, Andrei V. (Photonics Letters of Poland, 2013)
We design a plasmonic modulator which can be utilized as a compact active device in photonic integrated circuits. The active material, barium titanate (BaTiO3), is sandwiched between metal plates and changes its refractive index under applied voltage. Some degree of switching of ferroelectric domains from the in-plane to out-of-plane orientation provides the change of the refractive index, which can be exploited for effective light modulation. By numerical analysis we prove that the π phase change can be achieved with a 12…15 μm length device having propagation losses 0.05…0.2 dB/μm. Full Text: PDF References A.V. Zayats, I.I. Smolyaninov, and A.A. Maradudin, "Nano-optics of surface plasmon polaritons", Phys. Rep. 408, 131 (2005). CrossRef J.A. Schuller et al., "Plasmonics for extreme light concentration and manipulation", Nature Materials 9, 193 (2010). CrossRef D.K. Gramotnev and S.I. Bozhevolnyi, "Plasmonics beyond the diffraction limit", Nat. Photon. 4, 83 (2010). CrossRef K.F. MacDonald and N.I. Zheludev, "Active plasmonics: current status", Laser Photon. Rev. 4, 562–567 (2010). CrossRef V.J. Sorger, N.D. Lanzillotti-Kimura, Ren-Min Ma and Xiang Zhang, "Ultra-compact silicon nanophotonic modulator with broadband response", Nanophotonics 1, 17 (2012). CrossRef H.M.G. Wassel et al., "Opportunities and Challenges of Using Plasmonic Components in Nanophotonic Architectures", IEEE Journal on Emerging and Selected Topics in Circuits and Systems 2, 154-168 (2012). CrossRef W. Cai, J.S. White, and M.L. Brongersma, "Compact, High-Speed and Power-Efficient Electrooptic Plasmonic Modulators", Nano Letters 9, 4403 (2009). CrossRef J.A. Dionne, K. Diest, L.A. Sweatlock, and H.A. Atwater, "PlasMOStor: A Metal−Oxide−Si Field Effect Plasmonic Modulator", Nano Lett. 9, 897 (2009). CrossRef Wangshi Zhao and Zhaolin Lu, "Nanoplasmonic optical switch based on Ga-Si3N4-Ga waveguide", Optical Engineering 50, 074002 (2011). CrossRef B.A. Kruger et al., "Design of electrically driven hybrid vanadium dioxide (VO2) plasmonic switches", Optics Express 20, 23598 (2012). CrossRef A. Joushaghani et al., "Sub-volt broadband hybrid plasmonic-vanadium dioxide switches", Appl. Phys. Lett. 102, 061101 (2013). CrossRef J.A. Dionne, L.A. Sweatlock, H.A. Atwater, and A. Polman, "Plasmon slot waveguides: Towards chip-scale propagation with subwavelength-scale localization", Phys. Rev. B 73, 035407 (2006). CrossRef Y. Kurokawa and H.T. Miyazaki, "Metal-insulator-metal plasmon nanocavities: Analysis of optical properties", Phys. Rev. B 75, 035411 (2007). CrossRef Bozena Jaskorzynska, Yi Song, and Min Qiu, "Tradeoff between mode confinement, loss, and cross-talk, for dielectric and metal slot waveguides", Photonics Letters of Poland 1, 172 (2009). CrossRef A.V. Krasavin and A.V. Zayats, "Photonic Signal Processing on Electronic Scales: Electro-Optical Field-Effect Nanoplasmonic Modulator", Physical Review Letters 109, 053901 (2012). CrossRef A. Emboras et al., "Efficient coupler between silicon photonic and metal-insulator-silicon-metal plasmonic waveguides", Appl. Phys. Lett. 101, 251117 (2012). CrossRef A. Melikyan et al., "Surface plasmon polariton absorption modulator", Optics Express 19, 8855 (2011). CrossRef V.E. Babicheva and A.V. Lavrinenko, "Surface plasmon polariton modulator with optimized active layer", Proc. SPIE 8424, 842413 (2012). CrossRef V.E. Babicheva and A.V. Lavrinenko, "Plasmonic modulator optimized by patterning of active layer and tuning permittivity", Opt. Commun. 285, 5500 (2012). CrossRef Zhaolin Lu, Wangshi Zhao, and Kaifeng Shi, "Ultracompact Electroabsorption Modulators Based on Tunable Epsilon-Near-Zero-Slot Waveguides", IEEE Photonics Journal 4, 735 (2012). CrossRef V.E. Babicheva, I.V. Kulkova, R. Malureanu, K. Yvind, and A.V. Lavrinenko, "Plasmonic modulator based on gain-assisted metal–semiconductor–metal waveguide", Photonics and Nanostructures-Fundamentals and Applications 10, 389 (2012). CrossRef V.E. Babicheva, R. Malureanu, and A.V. Lavrinenko, "Plasmonic modulator based on thin metal-semiconductor-metal waveguide with gain core", Proc. SPIE 8627, 86270X (2013). CrossRef V.E. Babicheva, R. Malureanu, and A.V. Lavrinenko, "Plasmonic finite-thickness metal-semiconductor-metal waveguide as ultra-compact modulator", CrossRef A. Petraru, J. Schubert, M. Schmid, C. Buchal, "Ferroelectric BaTiO3 thin-film optical waveguide modulators", Appl. Phys. Lett. 81, 1375 (2002). CrossRef P. Tang, D.J. Towner, T. Hamano, A.L. Meier, B.W. Wessels, "Electrooptic modulation up to 40 GHz in a barium titanate thin film waveguide modulator", Opt. Express 12, 5962 (2004). CrossRef P. Tang, D.J. Towner, A.L. Meier, B.W. Wessels, "Low-voltage, polarization-insensitive, electro-optic modulator based on a polydomain barium titanate thin film", Appl. Phys. Lett. 85, 4615 (2004). CrossRef P. Tang, A.L. Meier, D.J. Towner, and B.W. Wessels, "BaTiO3 thin-film waveguide modulator with a low voltage-length product at near-infrared wavelengths of 0.98 and 1.55 µm", Optics Letters 30, 254 (2005). CrossRef I.D. Kim, Y. Avrahami, H.L. Tuller, Y.B. Park, M.J. Dicken, H.A. Atwater, "Study of orientation effect on nanoscale polarization in BaTiO3 thin films using piezoresponse force microscopy", Appl. Phys. Lett. 86, 192907 (2005). CrossRef M.J. Dicken, K. Diest, Y.B. Park, H.A. Atwater, "Growth and optical property characterization of textured barium titanate thin films for photonic applications", J. Cryst. Growth 300, 330 (2007). CrossRef M.J. Dicken et al., "Electrooptic Modulation in Thin Film Barium Titanate Plasmonic Interferometers", Nano Lett. 8, 4048 (2008). CrossRef P.B. Johnson and R.W. Christy, "Optical Constants of the Noble Metals", Phys. Rev. B 6, 4370 (1972). CrossRef A.D. Rakić, "Algorithm for the determination of intrinsic optical constants of metal films: application to aluminum", Appl. Opt. 34, 4755 (1995). CrossRef I.D. Rukhlenko, M. Premaratne, and G.P. Agrawal, "Guided plasmonic modes of anisotropic slot waveguides", Nanotechnology 23, 444006 (2012). CrossRef Shiyang Zhu, G. Q. Lo, and D. L. Kwong, "Theoretical investigation of silicon MOS-type plasmonic slot waveguide based MZI modulators", Optics Express 18, 27802 (2010). CrossRef Shiyang Zhu, G.Q. Lo, and D.L. Kwong, "Electro-absorption modulation in horizontal metal-insulator-silicon-insulator-metal nanoplasmonic slot waveguides", Appl. Phys. Lett. 99, 151114 (2011). CrossRef R. Thomas, Z. Ikonic, R.W. Kelsall, Photonics and Nanostructures – Fundamentals and Applications 10, 183 (2012). CrossRef